If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + -7)(3t + 9) = 0 Reorder the terms: (-7 + 8x)(3t + 9) = 0 Reorder the terms: (-7 + 8x)(9 + 3t) = 0 Multiply (-7 + 8x) * (9 + 3t) (-7(9 + 3t) + 8x * (9 + 3t)) = 0 ((9 * -7 + 3t * -7) + 8x * (9 + 3t)) = 0 ((-63 + -21t) + 8x * (9 + 3t)) = 0 (-63 + -21t + (9 * 8x + 3t * 8x)) = 0 Reorder the terms: (-63 + -21t + (24tx + 72x)) = 0 (-63 + -21t + (24tx + 72x)) = 0 (-63 + -21t + 24tx + 72x) = 0 Solving -63 + -21t + 24tx + 72x = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '63' to each side of the equation. -63 + -21t + 24tx + 63 + 72x = 0 + 63 Reorder the terms: -63 + 63 + -21t + 24tx + 72x = 0 + 63 Combine like terms: -63 + 63 = 0 0 + -21t + 24tx + 72x = 0 + 63 -21t + 24tx + 72x = 0 + 63 Combine like terms: 0 + 63 = 63 -21t + 24tx + 72x = 63 Add '-72x' to each side of the equation. -21t + 24tx + 72x + -72x = 63 + -72x Combine like terms: 72x + -72x = 0 -21t + 24tx + 0 = 63 + -72x -21t + 24tx = 63 + -72x Reorder the terms: -63 + -21t + 24tx + 72x = 63 + -72x + -63 + 72x Reorder the terms: -63 + -21t + 24tx + 72x = 63 + -63 + -72x + 72x Combine like terms: 63 + -63 = 0 -63 + -21t + 24tx + 72x = 0 + -72x + 72x -63 + -21t + 24tx + 72x = -72x + 72x Combine like terms: -72x + 72x = 0 -63 + -21t + 24tx + 72x = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-21 + -7t + 8tx + 24x) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-21 + -7t + 8tx + 24x)' equal to zero and attempt to solve: Simplifying -21 + -7t + 8tx + 24x = 0 Solving -21 + -7t + 8tx + 24x = 0 Move all terms containing t to the left, all other terms to the right. Add '21' to each side of the equation. -21 + -7t + 8tx + 21 + 24x = 0 + 21 Reorder the terms: -21 + 21 + -7t + 8tx + 24x = 0 + 21 Combine like terms: -21 + 21 = 0 0 + -7t + 8tx + 24x = 0 + 21 -7t + 8tx + 24x = 0 + 21 Combine like terms: 0 + 21 = 21 -7t + 8tx + 24x = 21 Add '-24x' to each side of the equation. -7t + 8tx + 24x + -24x = 21 + -24x Combine like terms: 24x + -24x = 0 -7t + 8tx + 0 = 21 + -24x -7t + 8tx = 21 + -24x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2(s+3)+4s-5=148+s | | 7h+9j-3h-j= | | 5x-4y=39 | | 4x+6-11x=8 | | 144x-54=18(8x-3) | | 4x-6x+21=5x+35 | | 4x-10+9+6x=34 | | x+1=3+x | | -8d+1=-3 | | 4(x-6)=-3x-17 | | 4x+8-7x+2=5x-8x+7 | | 24x-4+3=24x+12-10 | | 5-3n=10 | | 3x=12x^2 | | 80-k=41 | | 3x-4y=16*x | | 2x^2+4x-4=-6 | | 6(4b-2c)+9f= | | 5y^2-40y^2=0 | | 10(t-4)+4t=7(2t-5)-9 | | 6x+4=6x-9 | | 3x-6+4x-3=180 | | 6+7n=41 | | 2(2r+3)=10r | | 3ax-4x= | | 45+.02x=50+.3x | | 25x^2+y^2-100x-125=0 | | -9x^2-2x+4=8 | | 2X-3=20x | | 6(5-3y)=84 | | 5x+50y=16 | | 20.50x+150=903 |